Analisis Penerapan Konsep Green Business Pada Pengembangan UMKM Tahu Di Kota Medan: Ditinjau Dari Etika Bisnis Islam - Siregar, Rizky Anggina; Harahap, Muhammad Ikhsan; Silalahi, Purnama Ramadani (Jayapangus Press, 2024)
MSME activities generally have a positive impact on regional progress but also have a negative impact which creates conflict between the community and MSME owners. The resulting negative impacts result in environmental damage in the form of water pollution, air pollution, and so on which are detrimental to society. Tofu Entrepreneur MSMEs in Mabar Village, Medan Deli District, Medan City are MSMEs that have high productivity every day. This has a close relationship to the environmental and economic impacts of the surrounding community. The aim of this research is in accordance with the problem formulation that has been prepared, namely to determine the application of Green Business in the development of MSMEs. The type of research used in this research is descriptive research with a qualitative approach. The data sources obtained by researchers consist of 2 types, namely primary data in the form of interviews and secondary data in the form of literature or scientific articles and various related books. The data collection techniques and instruments used in this research are observation and interviews. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Based on the research results, it shows that the implementation of Green Business in tofu MSMEs in Mabar Village still does not fulfill the implementation of the 8 principles of implementing Green Business. The management of tofu production waste in this area is still lacking and not optimal because MSMEs know how to dispose of liquid waste by simply flowing it, causing an unpleasant odor. Judging from Islamic business ethics in implementing Green Business in MSMEs, it is known that in Mabar Village they have not fully implemented Islamic business ethics. The failure to implement Islamic business ethics by MSME players shows that the business practices carried out are not in accordance with Islamic law.